Investigating demotivational factors in Indonesian EFL classrooms: The case of madrasa students - Af'idatul Husniyah (Universitas Syiah Kuala, 2019)
Compared to motivation, demotivation is still a relatively new topic in the field of language learning. This present study aims to investigate demotivational factors among Madrasa (religious educational institution) students in the Indonesian EFL context. This study employed a mixed-methods approach with an explanatory design in which the quantitative phase was conducted before the qualitative phase. A 25-close-ended questionnaire along with one open-ended question were filled by 190 Madrasa students. To expand the results of the questionnaire, interviews with two students were conducted. Through a descriptive analysis and thematic analysis, five key demotivators were revealed, they are a) the nature of the target language, b) lesson-specific factors, c) learning materials, d) teacher-related factors, and e) the learning environment. The results also indicated some factors which are not included in the questionnaire, they are a) lack of self-confidence, b) lack of intrinsic motivation, c) lack of learning community, and d) teacher gender. Although previously students' religious beliefs were said to affect the students' demotivation, it appeared that half of the students did not consider them to be demotivating. Instead of religious beliefs, the students found the nature of English as the most demotivating factor, which contradicts the findings of previous demotivation studies that found teachers as the main demotivating factor.